A botanical collector abroad: contextualizing Thomas Penny's travels in Switzerland and France, 1565–1568. (18th February 2021) - Addyman, Marie
Abstract: Between 1565 and 1568 Thomas Penny travelled in Switzerland and France. The material he gathered and recorded served as annotations to Conrad Gessner's plant records. The intention to publish these edited notes as a collection was never realized, but Penny's journey clarifies many of the material circumstances under which collecting was undertaken.